QUALITATIVE AND QUANTITATIVE ANALYSIS OF FRUIT JUICE PACKAGED BEVERAGES - Sigiro, Mula; Alexander, Irving Josafat; Ginting, Rindang Leni Saputri; Sijabat, Naomi Christine (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2023)
Technological developments in the food sector make the appearance and packaging of food products more varied with the aim of attracting consumers to buy these products. Currently, canned food and beverage packaging dominates the market, not only in modern markets, but also in traditional markets. One of the packaged beverage products that is popular with the public is fruit juice packaging. This study aims to determine whether packaged fruit drinks circulating in the community comply with SNI 01-2981-1992 based on organoleptic parameters, pH value, sugar content, and vitamin C levels. Samples of packaged fruit drinks were randomly selected as many as 5 types of samples. This research uses qualitative and quantitative analysis approaches. From the results of the study, it can be concluded that the sample fruit juice packaging is suitable for consumption and meets the provisions of SNI 01-2981-1992.Keywords : fruit juice packaging, organoleptic, pH value, sugar content, vitamin C